2015
DOI: 10.1007/s11695-015-1972-4
|View full text |Cite
|
Sign up to set email alerts
|

Energy Adaptations Persist 2 Years After Sleeve Gastrectomy and Gastric Bypass

Abstract: Non-surgical weight loss induces a greater than expected decrease in energy expenditure, a phenomenon known as 'metabolic adaptation'. The effects of different bariatric surgery procedures on metabolic adaptation are not yet known and may partially contribute to weight loss success. We compared resting energy expenditure (REE) in 35 subjects (nine males; age = 46 ± 11 years; BMI = 42.1 ± 6.5 kg/m(2)) undergoing gastric band, sleeve gastrectomy or Roux-en-Y gastric bypass (RYGB) up to 2 years after surgery. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 11 publications
3
25
0
Order By: Relevance
“…The lack of significant AT after LRYGB and LAGB in our participants is in agreement with previous findings that measured and predicted RMR were not different after bariatric surgery (16, 17) but conflicts with some other reports (5, 13). These inconsistencies may be at least partially ascribed to methodological differences across studies.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The lack of significant AT after LRYGB and LAGB in our participants is in agreement with previous findings that measured and predicted RMR were not different after bariatric surgery (16, 17) but conflicts with some other reports (5, 13). These inconsistencies may be at least partially ascribed to methodological differences across studies.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, Tam et al (13) reported significant AT in 11 patients after six months with LRYGB (262±62 kcal/d) but not in 8 patients with LAGB (148±85 kcal/d). As with the study by Knuth et al (5), Tam et al (13) also did not have complete post-operative data for all participants from which the initial RMR prediction equation was developed.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In the first postoperative period, the energy demand is increasing, body temperature is growing, hyperventilation occurs and the energy is crucial to sustain proper tissue perfusion, ATP and phosphocreatine levels, and thus proper wound healing. The study of Tam et al shows, however, that the resting energy expenditure (REE) adaptation mechanism after both types of surgeries (SG and RYGB) does not contribute to body mass reduction, because REE lowers by 130–300 kcal/day and these are long-term changes—measurable even 2 years after the surgery [25]. …”
Section: Discussionmentioning
confidence: 99%